Analisis Kesiapan Fungsional Gerak Atlet Rugby Kabupaten Karawang Berdasarkan Functional Movement Screen - Ninda Sugi Nur Diyanti; Saryono; Habibi Hadi Wijaya (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the functional movement readiness of rugby athletes in Karawang Regency using the Functional Movement Screen (FMS) method as a basis for evaluating potential injury risk. This research used a descriptive method with a quantitative approach and an observational research design. The population consisted of 32 rugby athletes from Karawang Regency, and the sampling technique used was total sampling. The research instrument used the Functional Movement Screen test consisting of seven movement components: deep squat, hurdle step, inline lunge, shoulder mobility, active straight leg raise, trunk stability push-up, and rotary stability. Data were analyzed using descriptive statistics to determine the mean, minimum, and maximum scores of FMS. The results showed that the average FMS score of rugby athletes was 12.78 with a minimum score of 8 and a maximum score of 18. Based on the interpretation category of FMS scores, several athletes were categorized as having a moderate injury risk. The deep squat and active straight leg raise components had the highest average scores, while trunk stability push-up and rotary stability showed lower average scores. It can be concluded that the functional movement readiness of rugby athletes in Karawang Regency still needs improvement, particularly in core stability and movement control to minimize injury risk.